Histomorphometry of muscle fibers in breast fillets of broilers with wooden breast myopathy - Assunção, Andrey Sávio de Almeida; Garcia, Rodrigo Garófallo; Komiyama, Claudia Marie; Martins, Renata Aparecida; Caldara, Fabiana Ribeiro; Souza, Jacqueline Rosa de; Burbarelli, Maria Fernanda de Castro; Cavichiolo, Fabiana (Acta Scientiarum. Animal Sciences, 2023)
Wooden breast myopathy (WB) strongly affects the poultry industry mainly in terms of consumers rejection and economical loses, due to morphological changes in broiler muscle tissue and consequently low meat quality. The aim of this study is to evaluate the histomorphometry of muscle fibers of breast fillets of broilers with severity levels of WB myopathy. The histological evaluation considered 30 samples of the pectoralis major muscle and the level of WB myopathy (ten normal fillets, ten moderate fillets, and ten severe fillets). Fillets with a severe level of WB present low average fiber number, high average fiber diameter, low percentage of fibers with diameter of less than 20 µm, low percentage of fibers with diameter between 20 and 40 µm, and high percentage of fibers with diameter between 40 and 70 µm. Fiber cross-sectional area is greater in fillets affected by moderate and severe WB. Thus, fillets with a severe level of WB damage the muscle fiber structure and contribute more severely to the degenerative processes of breast meat.